2014
DOI: 10.1007/s12195-014-0373-4
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin-Mediated Signaling Regulates Cell Phenotype for Nucleus Pulposus Cells of the Intervertebral Disc

Abstract: Juvenile nucleus pulposus (NP) cells of the intervertebral disc (IVD) are large, vacuolated cells that form cell clusters with strong cell–cell interactions. With maturation and aging, NP cells lose their ability to form these cell clusters, with aging-associated changes in NP cell phenotype, morphology, and proteoglycan synthesis that may contribute to IVD degeneration. Therefore, it is important to understand the mechanisms governing juvenile NP cell cluster behavior towards the goal of revealing factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 49 publications
7
49
0
Order By: Relevance
“…This confirms the findings of previous studies that reported that mechanical overloading promoted matrix catabolism [11]. Previous studies have also indicated that N-CDH-mediated signaling promoted NP cell matrix production, whereas the blockage of N-CDH-mediated signaling resulted in the loss of NP cell matrix production [17, 18]. In line with this, we found that N-CDH overexpression partly promoted NP matrix biosynthesis under high-magnitude (20% deformation) compression, indicating that N-CDH plays an important role in resisting high-magnitude compression-induced NP matrix catabolism.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This confirms the findings of previous studies that reported that mechanical overloading promoted matrix catabolism [11]. Previous studies have also indicated that N-CDH-mediated signaling promoted NP cell matrix production, whereas the blockage of N-CDH-mediated signaling resulted in the loss of NP cell matrix production [17, 18]. In line with this, we found that N-CDH overexpression partly promoted NP matrix biosynthesis under high-magnitude (20% deformation) compression, indicating that N-CDH plays an important role in resisting high-magnitude compression-induced NP matrix catabolism.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have identified N-CDH expression in NP cells at either the transcriptional or protein level, regardless of animal species [15-18]. It is also worth mentioning that N-CDH expression decreases with disc aging and disc degeneration and that the decrease in N-CDH expression coincides with those degenerative disc changes [15, 16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N-CDH-mediated signaling is helpful to maintain a normal NP cell phenotype and NP matrix synthesis in vitro [29, 30]. In this study, N-CDH up-regulation coincided with better maintenance of the NP cell phenotype and NP matrix synthesis in the dynamic compression group.…”
Section: Discussionmentioning
confidence: 53%